230k views
0 votes
Solve please i need help

Solve please i need help-example-1

2 Answers

5 votes
Simplifying
8p + -4p = 2p + 6

Combine like terms: 8p + -4p = 4p
4p = 2p + 6

Reorder the terms:
4p = 6 + 2p

Solving
4p = 6 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
4p + -2p = 6 + 2p + -2p

Combine like terms: 4p + -2p = 2p
2p = 6 + 2p + -2p

Combine like terms: 2p + -2p = 0
2p = 6 + 0
2p = 6

Divide each side by '2'.
p = 3

Simplifying
p = 3
User Montresor
by
5.5k points
1 vote
I think the answer is P=3
User ManavM
by
4.8k points